NEUROPSYCHOLOGICAL ASSESSMENT IN THE ALZHEIMER DISEASE: EPISODIC AND SEMANTIC MEMORY - Ana Comesaña; Marcela González (CAEN, 2009)
This paper aims to review the neuropsychological evaluation process in Alzheimer (AD) patients, specifically that related to episodic and semantic memory. Alzheimer-style dementia is the main form of dementia, and is nowadays one of the most important social, cultural and health-related problems. Diagnosis and differentiation from normal aging are difficult in the initial stages, and so neuropsychological evaluation is key. The criteria currently utilized are those of the DSM IV (American Psychiatric Association, 1994) and of the NINCDS-ADRDA (Instituto Nacional para los Desórdenes Neurológicos, de la Comunicación y el Accidente Cerebro Vascular y la Asociación para la Enfermedad de Alzheimer y Desórdenes Relacionados) (McKhann G, Drachman D, Folstein M, y col., 1984), and they require that the diagnosis of probable AD be confirmed by neuropsychological evaluation in addition to clinical evaluation and other studies. After the division of long term memory into semantic and episodic memory was made, specific tests were created for their neuropsychological evaluation in different pathologies, including AD. An important contribution to the early detection of memory deterioration typical of such illness was thus made.